TM9SF1 expression correlates with autoimmune disease activity and regulates antibody production through mTOR-dependent autophagy - Juan Xiao; Zhenwang Zhao; Fengqiao Zhou; Jinsong Xiong; Zean Yang; Baoxian Gong; Lei Xiang; Mingming Liu; Fengsheng Cao; Hong Xiao; Huabo Chen; Anbing Zhang; et al. (BMC Medicine)
Abstract Background Transmembrane 9 superfamily member 1 (TM9SF1) is involved in inflammation. Since both inflammatory and autoimmune diseases are linked to immune cells regulation, this study investigated the association between TM9SF1 expression and autoimmune disease activity. As B cell differentiation and autoantibody production exacerbate autoimmune disease, the signaling pathways involved in these processes were explored. Methods Tm9sf1 −/− mouse rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) models were used to verify the relationship between gene expression and disease severity. Peripheral blood mononuclear cells (PBMCs) from 156 RA and 145 SLE patients were used to explore the relationship between TM9SF1 expression and disease activity. The effectiveness of TM9SF1 as a predictor of disease activity was assessed using multiple logistic regression and receiver operating characteristic (ROC) curves. The signaling pathways regulated by TM9SF1 in B cell maturation and antibody production were conducted by plasma cell induction experiment in vitro. Results The Tm9sf1 −/− RA and SLE model mice produced fewer autoantibodies and showed reduced disease severity relative to wild-type (WT) mice. TM9SF1 levels in PBMCs of patients were higher than those in healthy controls, and were reduced in patients with low disease activity relative to those with active RA and SLE. Furthermore, TM9SF1 levels were positively linked with autoantibody titers and pro-inflammatory cytokine levels in both diseases. ROC analyses indicated TM9SF1 outperformed several important clinical indicators in predicting disease activity (area under the curve (AUC) were 0.858 and 0.876 for RA and SLE, respectively). In vitro experiments demonstrated that Tm9sf1 knockout blocked differentiation of B cells into antibody-producing plasma cells by activating mTOR and inhibiting autophagy, and mTOR inhibitors such as rapamycin could reverse this effect. Conclusions The primary finding was the identification of the molecular mechanism underlying autophagy regulation in B cells, in which Tm9sf1 knockout was found to modulate mTOR-dependent autophagy to block B cell differentiation into antibody-secreting plasma cells. It was also found that TM9SF1 expression level in PBMCs was an accurate indicator of disease activity in patients with RA and SLE, suggesting its clinical potential for monitoring disease activity in these patients.